Perspectives of microbial oils for biodiesel production - Li, Qiang; Du, Wei; Liu, Dehua (Applied microbiology and biotechnology, 2008)
Biodiesel has become more attractive recently because of its environmental benefits, and the fact that it is made from renewable resources. Generally speaking, biodiesel is prepared through transesterification of vegetable oils or animal fats with short chain alcohols. However, the lack of oil feedstocks limits the large-scale development of biodiesel to some extent. Recently, much attention has been paid to the development of microbial, oils and it has been found that many microorganisms, such as algae, yeast, bacteria, and fungi, have the ability to accumulate oils under some special cultivation conditions. Compared to other plant oils, microbial oils have many advantages, such as short life cycle, less labor required, less affection by venue, season and climate, and easier to scale up. With the rapid expansion of biodiesel, microbial oils might become one of potential oil feedstocks for biodiesel production in the future, though there are many works associated with microorganisms producing oils need to be carried out further. This review is covering the related research about different oleaginous microorganisms producing oils, and the prospects of such microbial oils used for biodiesel production are also discussed.